OPTIMALISASI LAYANAN BERBASIS SYARIAH DI CINNAMON HOTEL BOUTIQUE - Caniago, Fauzi; Ghina Salsabila, Ananda; Sari Pusti, Restya (LPPM Politeknik Pajajaran ICB, 2024)
Optimization of Sharia-compliant services in the hospitality industry is becoming increasingly important due to the rising number of Muslim travelers. Cinnamon Hotel Boutique endeavors to meet this demand by offering services that adhere to Sharia principles. The aim of this research is to enhance the quality of Sharia-based services at Cinnamon Hotel Boutique to improve the satisfaction of Muslim guests and ensure adherence to Islamic values. This research employs a qualitative descriptive approach to examine the current conditions or natural phenomena related to Cinnamon Hotel Boutique. The findings indicate that: Optimization of Sharia-based services at Cinnamon Hotel Boutique includes: Mandatory requirement for guests to stay with a mahram, Adhan and recitation of Quranic verses through speakers in each room and public areas, Timely congregational prayers, Provision of prayer equipment in each room, Live broadcasts of Medina and Mecca on TV, Tahajjud wake-up call (upon request), Welcome drink of Zamzam water and dates, 100% Halal dining options, and Guests staying at the hotel are given cinnamon tree souvenirs upon check-out. The optimization of Sharia-based services at Cinnamon Hotel Boutique has successfully increased guest satisfaction. Recommendations for further development include expanding Sharia-compliant facilities and enhancing promotional efforts.